Removing Hand Form Information Specifically Impairs Emotion Recognition for Fearful and Angry Body Stimuli. (January 2020) - Ross, Paddy; Flack, Tessa
Emotion perception research has largely been dominated by work on facial expressions, but emotion is also strongly conveyed from the body. Research exploring emotion recognition from the body tends to refer to "the body" as a whole entity. However, the body is made up of different components (hands, arms, trunk, etc.), all of which could be differentially contributing to emotion recognition. We know that the hands can help to convey actions and, in particular, are important for social communication through gestures, but we currently do not know to what extent the hands influence emotion recognition from the body. Here, 93 adults viewed static emotional body stimuli with either the hands, arms, or both components removed and completed a forced-choice emotion recognition task. Removing the hands significantly reduced recognition accuracy for fear and anger but made no significant difference to the recognition of happiness and sadness. Removing the arms had no effect on emotion recognition accuracy compared with the full-body stimuli. These results suggest the hands may play a key role in the recognition of emotions from the body.